The Landscape of Capital Flows to Low-Income Countries - Dorsey, Thomas (IMF Working Papers; Working Paper ;, 2008)
This paper reviews trends in capital flows and capital-like flows such as official grants and remittances to low-income countries over the period 1981-2006. The survey reveals a broadbased increase in such flows as a share of low-income country GDP across major regions, countries with differing commodity export composition, and countries with differing debt relief status. The increase in inflows is dominated by an increase in private sector inflows, mostly in the form of private transfers and foreign direct investment. Official sector inflows have remained comparatively constant as a share of low-income country GDP and even declined in the most recent years. The paper concludes with some tentative policy conclusions and has a discussion of data issues in the annexes.